Prevalence and Association of Atypical Cervical Epithelial Cell Abnormalities with Different SociodemographicFactors among Women Attending theMaternity Teaching Hospital inErbil, Iraq. - Runak Ali Ismail; Samira Salim Shekh Mohammad; Zahida Haris Saeed (Diyala Journal of Medicine, 2019)
Background: Regular Pap smear screening leads to significant decreases in morbidity and mortality from cervical cancer.